Conversão de uma histidina amônia liase para fenilalanina amônia liase por meio de biologia sintética - Santos Júnior, Célio Dias (2016)
Phenylalanine ammonia lyase (PAL) catalyzes the non-oxidative deamination of L-Phe. It is an important enzyme in the production of enantio-pure mixtures of phenylalanine. Besides being important in plant secondary metabolism, PAL has also been used both for industrial applications as in the treatment of leukemia and phenylketonuria. The PAL have high similarity with histidine ammonia lyase (HAL) and it is believed that the PAL originated from HAL. Use of HAL termini sequences, previously obtained from the metagenome of Poraquê Lake (03°57' S, 63°10' W) to produce an engineered enzyme. The HAL assembled from them had its catalytic core exchanged by one which was designed from the previously described PAL sequences. Thus, We aim to shift the HAL activity making it active in the presence of phenylalanine through an easy protocol. Our phylogenetic analysis shows a clear division between plant and fungal PALs, and showed that recombination played a key role in the separation of these groups. In addition, We also observed that PAL catalytic core is conserved despite positive selection operating in protein termini. The recombinant enzyme, mPAL_c1, was produced in insoluble form and was refolded in vitro. mPAL_c1, when using L-Phe as substrate, has a TOPT. of 30°C (at pH 7.5 with 2mM MnCl2), KM of 55μM and Kcat/KM of 0.01633 mM-1s-1. The activity of mPAL_c1 showed about 30% of activity of commercial PAL from Rhodotorula toruloides at 2 mM L-Phe. Activation of mPAL_c1 was tested through substrate concentration rising from 2 mM to 5 mM of L-Phe, and its activity was almost 5 times higher. The results still suggest a histidine ammonia lyase remnant activity. The low catalytic rates are justified due to protein aggregation and misfolding, detected by size exclusion chromatography and by circular dichroism. In summary, our protocol has proved to be useful in protein design.